Marketing management : A south asian perspective - Kotler, Philip (Delhi : Pearson, 2013)
Key Features: * Brand new chapter-opening vignettes that can serve as great classroom discussion starters. * Updated and revised Marketing Memo and Marketing Insight boxes that provide in-depth insights into the practical aspects of marketing and discuss the challenges and opportunities unique to rural markets in South Asia. * Many new in-text cases, in addition to Marketing Excellence cases at the end of each chapter. * Dramatic changes in the current marketing environment addressed through subsections on issues such as marketing during economic downturns, the rise
Appendix A-1-13p.; Glossary G-1-9p.; Index I-1-20p.
Keywords: Analyzing business markets; Scanning the marketing; Creating customer value